Rāingān kānwičhai kānl̄ưaktang samāchik saphā thētsabān 118 h̄æng, m̄ưa wanthī 23 Thanwākhom 2510 (ʻAmarin Phrinting ʻ̄æn Phaplitching, 1997)
Report on municipal government election of 23rd December 1967 from 118 polls, Thailand.